Nanoscale structural analysis of Bi0.5Na0.5TiO3 in high-temperature phases. (23rd August 2021) - Yoneda, Yasuhiro; Noguchi, Yuji
Abstract: We performed a local structure analysis of the ferroelectric perovskite Bi0.5 Na0.5 TiO3 (BNT) in high-temperature tetragonal and cubic phases by combining high-energy synchrotron X-ray diffraction and atomic pair-distribution function. BNT is a promising lead-free piezoelectric material, although it has the problem of narrow working temperature range due to its low depolarization temperature. Since the depolarization temperature of BNT is caused by a diffuse order-disorder phase transition similar to a relaxer ferroelectrics, local structural analysis over a wide temperature range is required to elucidate the depolarization phenomenon. Using this approach, we found that the local structure is largely contributed by the diffuse component, and the deviation from the average structure is caused by the shift of Bi atoms. The amount of shift increased with increasing temperature. Changes in nanoscale structure with distance are closely related to BNT depolarization phenomena. The results show the model needed to develop highly functional piezoelectric materials.